A new unified theory of sociobehavioral forces - Guillermina Jasso (Institute for the Study of Labor (IZA), 2007)
This paper proposes a new unified theory of sociobehavioral forces. The goal of the new theory is to integrate theories describing five sociobehavioral processes - comparison (including justice and self-esteem), status, power, identity, and happiness - bringing under a single theoretical umbrella diverse mechanisms together with their effects across disparate domains and for both individuals and societies. The integration is made possible by the remarkable similarity of the internal core of the theories, a core comprised of three elements: personal quantitative characteristics, personal qualitative characteristics, and primordial sociobehavioral outcomes. The unified theory posits the operation of three sociobehavioral forces - comparison, status, and power - each associated with a distinctive mechanism, in particular, a distinctive rate of change of the outcome with respect to the quantitative characteristic. Each combination of elements - e.g., status-wealth-city - generates a distinctive identity and a distinctive magnitude of happiness. Thus, the theory enables systematic and parsimonious analysis of both individuals and societies via the distinctive configurations of elements. To illustrate the unified theory, we analyze the three-way contest between loyalty to self, subgroup, and group in a two-subgroup society, deriving many new testable predictions, for example, that the bottom subgroup will have difficulty mobilizing itself, that the ablest individuals in a society will not make good leaders as their first loyalty is to self, and that the proportions loyal to self, subgroup, and group differ sharply, depending on the sociobehavioral forces, valued goods, and subgroup size. Finally, the theory provides a foundation for making explicit connections among the most important themes and insights of contemporary social science, including inequality, oppositional culture, group boundary permeability, social inclusion and exclusion, segregation and integration, social distance and polarization, and bonding and bridging.
Keywords: C02; 300; Justice; comparison; status; power; identity; happiness; inequality; personal quantitative characteristics; personal qualitative characteristics; individualism and collectivism; lognormal distribution; Pareto distribution; power-function distribution; rectangular distribution; exponential distribution; normal distribution; Soziales Verhalten; Verhalten; Theorie